Antibacterial activity of alkaloid extracts from Ochrosia oppositifolia - Puteri I.A.M. Mahmud,; W.A. Yaacob,; Nazlina Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Ochrosia oppositifolia can be found along the coastline and is locally known as ‘Mempelam pasih’ or ‘Mangga laut’. In this study, the alkaloids from the leaves, stem-bark and roots were extracted and tested for their antibacterial activity. So far, no previous studies have been carried out to determine the antibacterial potential of the extracts. Each extract was tested using disc-diffusion and minimum inhibitory concentration (MIC) methods. The highest inhibitory diameters shown by 10 mg/mL extracts of the leaves and stem-bark against Staphylococcus aureus and the roots against MRSA were 10.0±2.8 and 10.5±2.1 and 14.0±2.8 mm. On the other hand, the MIC values exhibited by the leaf and stem-bark extracts against Bacillus subtilis, Salmonella thyphimurium and Serratia marcescens and the root extract against Vibrio fluvialis were 3.75 and 0.94 and 0.12 mg/mL. This study broadens the bioactivity potential of the plant and the information obtained can be utilized for pharmacological purposes.